2021
DOI: 10.48550/arxiv.2112.08866
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detecting Model Misspecification in Amortized Bayesian Inference with Neural Networks

Abstract: Neural density estimators have proven remarkably powerful in performing efficient simulation-based Bayesian inference in various research domains. In particular, the BayesFlow framework uses a two-step approach to enable amortized parameter estimation in settings where the likelihood function is implicitly defined by a simulation program. But how faithful is such inference when simulations are poor representations of reality? In this paper, we conceptualize the types of model misspecification arising in simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…2d, see Supplementary material for details). Recent methodological work in SBI addresses this problem, e.g., by automatically detecting model misspecification ( Schmitt et al, 2022 ) or by explicitly incorporating the model mismatch into the generative model ( Ward et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…2d, see Supplementary material for details). Recent methodological work in SBI addresses this problem, e.g., by automatically detecting model misspecification ( Schmitt et al, 2022 ) or by explicitly incorporating the model mismatch into the generative model ( Ward et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has found neural SBI methods behave poorly under model misspecification (Bon et al, 2022;Cannon et al, 2022;Schmitt et al, 2021;Ward et al, 2022). It is not surprising that neural SBI methods suffer from the same issues as ABC and BSL when compatibility is not satisfied as they are based on many of the same principles.…”
Section: Robust Extension To Sequential Neural Likelihoodmentioning
confidence: 99%
“…Recently, methods have been developed to detect model misspecification when applying neural posterior estimation for both amortised (Ward et al, 2022) and sequential (Schmitt et al, 2021) approaches. 1 Schmitt et al (2021) use a maximum mean discrepancy (MMD) estimator to detect a "simulation gap" between the observed and simulated data.…”
Section: Robust Extension To Sequential Neural Likelihoodmentioning
confidence: 99%
See 2 more Smart Citations